Beyond technology adoption: Analysis of student experiences in virtual learning environments at a Latin American University - Mamani-Flores, Adderly; Apaza-Ticona, Jorge; Apaza-Chino, Julian; Maquera-Maquera, Yuselino; Zegarra-Ugarte, Soledad Jackeline (International Journal of Innovative Research and Scientific Studies, 2025)
Virtual Learning Environments (VLEs) have become critical in higher education, yet student experiences in resource-constrained contexts remain understudied. This study examines the perceptions, usage patterns, and satisfaction of social sciences students at Peru’s National University of the Altiplano (UNA) with VLEs, identifying barriers to their effectiveness. A stratified random sample of 112 mid-to-upper-year undergraduates (semesters 4–8) completed a cross-sectional survey, analyzed via descriptive and correlational statistics. Results revealed that 57.1% of students rated their VLE experience positively, valuing access to materials and peer-teacher interaction. However, 50.9% faced recurrent technical issues, and 38.4% perceived VLEs as less effective than face-to-face instruction. Dominant tools included Zoom and Google Meet, but gaps emerged in personalized support and technical troubleshooting. While VLEs are recognized as useful for learning, the findings highlight systemic challenges: inadequate digital training and limited interaction design. The study proposes targeted interventions—enhanced instructor/student training and iterative platform improvements—to optimize VLE efficacy in underserved higher education settings.